2008
DOI: 10.1007/978-1-84628-885-2_16
|View full text |Cite
|
Sign up to set email alerts
|

CARO – The Common Anatomy Reference Ontology

Abstract: Summary. The Common Anatomy Reference Ontology (CARO) is being developed to facilitate interoperability between existing anatomy ontologies for different species, and will provide a template for building new anatomy ontologies. CARO has a structural axis of classification based on the top-level nodes of the Foundational Model of Anatomy. CARO will complement the developmental process sub-ontology of the GO Biological Process ontology, using the latter to ensure the coherent treatment of developmental stages, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 17 publications
0
83
0
Order By: Relevance
“…Although Ogloblin (1944) suggested that Waterston's structure might have glandular function, he never described any corresponding glands and applied the term "Waterston's organ" exclusively to the cuticle modifi cation. According to the Common Anatomy Reference Ontology (Haendel et al 2007) a simple organ is a multi-tissue structure. Because this cuticular modifi cation is not a multi-tissue structure we prefer to replace "organ" with "evaporatorium" from the heteropterists' lexicon.…”
Section: Methodsmentioning
confidence: 99%
“…Although Ogloblin (1944) suggested that Waterston's structure might have glandular function, he never described any corresponding glands and applied the term "Waterston's organ" exclusively to the cuticle modifi cation. According to the Common Anatomy Reference Ontology (Haendel et al 2007) a simple organ is a multi-tissue structure. Because this cuticular modifi cation is not a multi-tissue structure we prefer to replace "organ" with "evaporatorium" from the heteropterists' lexicon.…”
Section: Methodsmentioning
confidence: 99%
“…Some ontologies represent structure, others represent function, yet others represent stages of development, and some draw on combinations of these, in ways that close off opportunities for automatic reasoning. The Foundry has created a roadmap for the incremental resolution of this problem through the initiation of the Common Anatomy Reference Ontology (CARO) 14 , which is providing guidelines both for modelorganism communities with legacy anatomy ontologies who wish to initiate reforms in the direction of compatibility and for communities who wish to build new ontologies from scratch. CARO is based on the toplevel types of the FMA and is serving as a template for the creation of the Fish Multi-Species, Ixodidae and Argasidae (tick), mosquito and Xenopus anatomy ontologies, and also as basis for reforms of the Drosophila and zebrafish anatomy ontologies 19 .…”
Section: Progress Thus Farmentioning
confidence: 99%
“…BSPO classes for ‘anatomical compartment’ and ‘anatomical compartment boundary’ (11 classes) refer to anatomical structures defined by lineage restriction [6] rather than by axial position, and thus these classes will be moved to the Common Anatomy Reference Ontology (CARO) [7] in the future. Individual compartments and their boundaries are typically named with respect to some axis.…”
Section: Resultsmentioning
confidence: 99%